2014
DOI: 10.1021/bi401223r
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Levels of Sequence Selectivity and Catalytic Efficiency of Protein-Tyrosine Phosphatases

Abstract: The sequence selectivity of 14 classical protein-tyrosine phosphatases (PTPs) (PTPRA, PTPRB, PTPRC, PTPRD, PTPRO, PTP1B, SHP-1, SHP-2, HePTP, PTP-PEST, TCPTP, PTPH1, PTPD1, and PTPD2) was systematically profiled by screening their catalytic domains against combinatorial peptide libraries. All of the PTPs exhibit similar preference for pY peptides rich in acidic amino acids and disfavor positively charged sequences, but differ vastly in their degrees of preference/disfavor. Some PTPs (PTP-PEST, SHP-1, and SHP-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 72 publications
3
45
0
Order By: Relevance
“…We tested tyrosine to phenylalanine mutations (Y>F mutations) in the chimeric Met-Dscam1 receptor assay and found that five tyrosine mutations (Y1707F, Y1857F, Y1890F, Y1911F and Y1981F) significantly reduced Met-Dscam1 baseline phosphorylation (Figure 4B, 4C, S4B) while the Y1857F and Y1890F mutations also showed strong reduction of ligand-induced Met-Dscam1 activation (Figure 4B, 4C). Further sequence motif analysis suggests that Y1857, Y1890, and Y1911, are potential RPTP substrate sites (Figure 4D, S4D) (Ren et al, 2011; Selner et al, 2014; Tonks, 2013). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We tested tyrosine to phenylalanine mutations (Y>F mutations) in the chimeric Met-Dscam1 receptor assay and found that five tyrosine mutations (Y1707F, Y1857F, Y1890F, Y1911F and Y1981F) significantly reduced Met-Dscam1 baseline phosphorylation (Figure 4B, 4C, S4B) while the Y1857F and Y1890F mutations also showed strong reduction of ligand-induced Met-Dscam1 activation (Figure 4B, 4C). Further sequence motif analysis suggests that Y1857, Y1890, and Y1911, are potential RPTP substrate sites (Figure 4D, S4D) (Ren et al, 2011; Selner et al, 2014; Tonks, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…(n=5 for YF1707 and YF1911; n=4 for YF1857; n=3 for YF1890 and YF1981; ANOVA/Dunnett to compare the phosphorylation state of Met-Dscam1 in presence and absence of HGF: * or ° P ≤ 0.05; ** P ≤ 0.01; *** P ≤ 0.001). (D) Sequence alignment of the 5 candidate RPTP69D and known PTP tyrosine substrate residues (Selner et al 2014). Substrate tyrosines (magenta).…”
Section: Figurementioning
confidence: 99%
“…Analysis of the selectivity of PTPRD's D1 phosphatase domain reveals (1) lack of a highly specific consensus sequence for the amino acids that surround the phosphotyrosine; (2) preference for large hydrophobic amino acids, especially adjacent (–1) to the phosphotyrosine; (3) preference for acidic residues in the vicinity of the phosphotyrosine; (4) aversion to basic residues at these locations; (5) relatively lower affinity for phosphotyrosine substrates when compared with the affinities of other protein tyrosine phosphatases; and (6) good catalytic activities (k cat values) that are close to those of other protein tyrosine phosphatases and thus the potential to act as a highly efficient enzyme with a high k cat / K M ratio …”
Section: What Is Ptprd?mentioning
confidence: 99%
“…We chose to study EGFR as a model PTK because its preference for highly acidic peptide substrates 31,32 results in significant overlap both in the sequences of Htc-tide and Tyr-tide and also in the recognition motifs of many PTPases. 24 Additionally, EGFR is an established oncogene and drug target in many epithelium-derived cancers, where single-cell EGFR activity measurements pose an exciting analytical challenge to which directed metabolic cytometry is uniquely suited. We used a CE-LIF-based in vitro assay and progress curve analysis to model Htc-tide and Tyr-tide phosphorylation by the recombinant EGFR kinase domain according to the Michaelis–Menten kinetic model (Methods and Supporting Information).…”
Section: Resultsmentioning
confidence: 99%